Climate shapes the seed germination niche of temperate flowering plants: a meta-analysis of European seed conservation data - Carta, Angelino; Fernández-Pascual, Eduardo; Gioria, Margherita; Müller, Jonas V; Rivière, Stéphane; Rosbakh, Sergey; Saatkamp, Arne; Vandelook, Filip; Mattana, Efisio (Annals of botany, 2022)
BACKGROUND AND AIMS: Interactions between ecological factors and seed physiological responses during the establishment phase shape the distribution of plants. Yet, our understanding of the functions and evolution of early-life traits has been limited by the scarcity of large-scale datasets. Here, we tested the hypothesis that the germination niche of temperate plants is shaped by their climatic requirements and phylogenetic relatedness, using germination data sourced from a comprehensive seed conservation database of the European flora (ENSCOBASE). METHODS: We performed a phylogenetically informed Bayesian meta-analysis of primary data, considering 18 762 germination tests of 2418 species from laboratory experiments conducted across all European geographical regions. We tested for the interaction between species' climatic requirements and germination responses to experimental conditions including temperature, alternating temperature, light and dormancy-breaking treatments, while accounting for between-study variation related to seed sources and seed lot physiological status. KEY RESULTS: Climate was a strong predictor of germination responses. In warm and seasonally dry climates the seed germination niche includes a cold-cued germination response and an inhibition determined by alternating temperature regimes and cold stratification, while in climates with high temperature seasonality opposite responses can be observed. Germination responses to scarification and light were related to seed mass but not to climate. We also found a significant phylogenetic signal in the response of seeds to experimental conditions, providing evidence that the germination niche is phylogenetically constrained. Nevertheless, phylogenetically distant lineages exhibited common germination responses under similar climates. CONCLUSION: This is the first quantitative meta-analysis of the germination niche at a continental scale. Our findings showed that the germination niches of European plants exhibit evolutionary convergence mediated by strong pressures at the macroclimatic level. In addition, our methodological approach highlighted how large datasets generated by conservation seed banking can be valuable sources to address questions in plant macroecology and evolution.
Keywords: semena rostlinná; Plants; Temperature; Plant Dormancy; Bayes Theorem; fylogeneze; klíčení; Phylogeny; Germination; Climate; Seeds; vegetační klid; rostliny; germination; seed dormancy; evolution; plant regeneration; Magnoliopsida; Bayesova věta; macroecology; seed trait; ENSCONET; teplota